Effects of growth regulators on seed germination, seedling growth and some aspects of metabolism of Wheat under allelochemical stress - Unal, Bengu Turkyilmaz (Bangladesh Journal of Botany, 2013)
Effects of growth regulators on seed germination, seedling growth and some aspects of metabolism of wheat under allelochemical stress due to oleander and walnut leaf (extract and powder) were investigated. All parameters e.g. seed germination, seedling growth, leaf pigments except the proline content reduced significantly under stress. On the contrary, GA3 and IBA showed alleviating activities. The alleviation effect of GA3 was higher than that of IBA . DOI: http://dx.doi.org/10.3329/bjb.v42i1.15865 Bangladesh J. Bot. 42(1): 65-71, 2013 (June)